Regulation of neonatal IgA production by the maternal microbiota - Mu, Qinghui (Proc Natl Acad Sci U S A, 2021)
Infants are prone to enteric infections due to an underdeveloped immune system. The maternal microbiota, through shaping the neonatal microbiota, helps establish a strong immune system in infants. We and others have observed the phenomenon of enhanced early neonatal immunoglobulin A (IgA) production in preweaning immunocompetent mice nursed by immunodeficient dams. Here, we show that this enhancement of IgA in neonates results from maternally derived microbiota. In addition, we have found that the neonatal IgA production can be induced by Lactobacillus reuteri, which is enriched in the milk of immunodeficient dams. Moreover, we show that while the production of neonatal IgA is dependent on neonatal T cells, the immunodeficient maternal microbiota-mediated enhancement of neonatal IgA has a T cell–independent component. Indeed, this enhancement may be dependent on type 3 innate lymphoid cells in the neonatal small intestinal lamina propria. Interestingly, maternal microbiota-induced neonatal IgA does not cross-react with common enteric pathogens. Future investigations will determine the functional consequences of having this extra IgA.